Gender roles stereotypes in the workplace (2016)
This literary review explores the concepts of gender, sex, stereotype, and gender roles, applied to the workspace. It is important to make the distinction between the first two terms, as they are often confused among people. Besides, this paper is focused on how gender role stereotypes influence all the processes involved in the work areas: from applying to a job, to the opportunities to advance once a person is already working in a company. Given that women are the most affected by these kinds of stereotypes, it has been necessary to study -in a brief way-, some historical moments of women’s struggle to get to the same level as men in every possible aspect in the social context. In conclusion, this paper enabled the identification of gender roles stereotypes and their relevance in the work field in present days; as they lead to prejudices when meeting other people; and the division of professions into masculine and feminine these roles make, affects in a major way people’s job opportunities and career development.